2018
DOI: 10.1002/jcp.27518
|View full text |Cite
|
Sign up to set email alerts
|

Matrix stiffness modulates the differentiation of neural crest stem cells in vivo

Abstract: Stem cells are often transplanted with scaffolds for tissue regeneration; however, how the mechanical property of a scaffold modulates stem cell fate in vivo is not well understood. Here we investigated how matrix stiffness modulates stem cell differentiation in a model of vascular graft transplantation. Multipotent neural crest stem cells (NCSCs) were differentiated from induced pluripotent stem cells, embedded in the hydrogel on the outer surface of nanofibrous polymer grafts, and implanted into rat carotid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 37 publications
6
27
0
Order By: Relevance
“…These findings suggest that surfaces of certain stiffness can improve the specificity and homogeneity of differentiated neural stem cells. This interpretation is supported by recent findings showing that human induced pluripotent stem cell-derived neural crest stem cells implanted into the rat carotid artery preferentially differentiate to smooth muscle cells in a stiff environment, and to glial cells under softer conditions (Zhu et al, 2019).…”
supporting
confidence: 61%
See 2 more Smart Citations
“…These findings suggest that surfaces of certain stiffness can improve the specificity and homogeneity of differentiated neural stem cells. This interpretation is supported by recent findings showing that human induced pluripotent stem cell-derived neural crest stem cells implanted into the rat carotid artery preferentially differentiate to smooth muscle cells in a stiff environment, and to glial cells under softer conditions (Zhu et al, 2019).…”
supporting
confidence: 61%
“…Previous studies have shown that embryonic stem cells grown on stiff substrates maintain their proliferative capacity, but undergo (Panciera, Azzolin, Cordenonsi, & Piccolo, 2017). However, there is not a straightforward relationship between mechanical conditions in the environment and stem cell differentiation, since, for example, mesenchymal stem cells (McBeath, Pirone, Nelson, Bhadriraju, & Chen, 2004;Panciera et al, 2017) and neural crest stem cells (Zhu et al, 2019) Laminin provided good conditions for cell adhesion regardless of PAA stiffness, although with a moderate, but still significant, decline with the highest scaffold stiffness. Interestingly, this decline did not negatively affect bNCSC maintenance, which was, in fact, best on high stiffness laminin substrate.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Poly l-lactide (PLLA) (1.09 dL/g inherent viscosity, Lactel Absorbable Polymers) was dissolved in 1,1,1,3,3hexafluoro-2-propanol (HFIP; Matrix Scientific) by means of sonication for 30 min or until all of the PLLA crystals were completely dissolved, resulting in 19% (w/v) solution. Nonwoven aligned nanofibrous vascular scaffolds composed of PLLA were fabricated using a customized electrospinning process [9]. In brief, a voltage of 12 kV was applied through a high-voltage generator (Gamma High Voltage) to a spinneret that was aimed at a grounded, rotating, stainless steel mandrel (1mm diameter; 150 revolutions/min).…”
Section: Scaffold Fabricationmentioning
confidence: 99%
“…T he recent prominent discovery of induced pluripotent stem cells (iPSCs), which are reprogrammed from adult somatic cells, has shown promise for use in the field of regenerative medicine [1,2], and there is evidence that iPSCs can serve as an advanced cell source for vascular engineering [3][4][5][6][7]. The biophysical properties such as the stiffness and micro-/nanotopography play important roles in regulating cell functions and tissue remodeling [8][9][10]. Neural crest stem cells (NCSCs) derived from iPSCs are multipotent, and can differentiate into both mesenchymal and neural lineages, which represent a valuable cell source for tissue engineering and blood vessel regeneration in vitro and in vivo [11,12].…”
Section: Introductionmentioning
confidence: 99%